PENGARUH INTELLECTUAL CAPITAL TERHADAP RETURN ON ASSETS - Dwi Urip Wardoyo; Amalia Cahya Rini; Ade Amara Dini (Jurnal Akuntansi dan Keuangan (JAK), 2022)
Return on Assets is one of the indicators that can be used to measure how effectively a company utilizes its assets to generate profits and achieve competitive advantage in its performance. The Resources-Based Theory explains that the use of resources effectively and efficiently can be a competitive advantage for a company. Intellectual capital is a resource in the form of intangible assets that are believed to be able to create added value for an entity through the Value Added Intellectual Capital (VAIC™) method. Therefore, this study aims to determine the effect of Intellectual Capital as proxy for Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA) on Return on Assets (ROA). This research is in the form of quantitative research using descriptive statistical analysis methods and panel data regression analysis with secondary data sources and samples from mining sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The results showed that simultaneously VACA, VAHU and STVA had a significant effect on ROA. However, partially VACA showed a significant negative effect on ROA, VAHU had a significant positive effect on ROA, and STVA did not have a significant effect on ROA.